THE ROLE OF WOMEN AND ACCESS TO FINANCE IN STRENGTHENING SOCIAL RESILIENCE AND ECONOMIC INNOVATION IN COASTAL COMMUNITIES - R. Abdoel Djamali; Dhanang Eka Putra; Deltaningtyas Tri Cahyaningrum; Naning Retnowati; Amalia Dwi Marseva (Juremi: Jurnal Riset Ekonomi, 2025)
This study investigates how women’s economic roles and access to finance shape social resilience and economic innovation in coastal communities. Focusing on 55 households in Puger District, Indonesia, the research adopts an explanatory survey design using a structured questionnaire to measure women’s roles, access to finance, social resilience, and economic innovation on a five-point Likert scale. Descriptive statistics show that women play a strong role in household and community economies, while access to finance and innovation remain at moderate levels. Multiple linear regression reveals that women’s roles and access to finance both have significant positive effects on social resilience, alongside education and income. A second model demonstrates that women’s roles, access to finance, and social resilience jointly and significantly predict economic innovation, with social resilience emerging as a particularly strong determinant. These findings suggest that women’s participation and inclusive financial services are not only crucial for short-term welfare, but also for building the adaptive capacity and innovation needed to transform coastal livelihoods. The study recommends gender-responsive financial schemes and institutional support that strengthen social networks, collective learning, and experimentation as strategic pathways for enhancing resilience and innovation in coastal areas.